Kemampuan Cukil Kayu Mahasiswa Pendidikan Seni Rupa Fakultas Seni dan Desain Universitas Negeri Makassar - Dwi Wahyuni Hamka; Faidhul Inayah (Nuansa Journal of Arts and Design, 2023)
This study aims to determine the level of ability of students of class 2011 of the Fine Arts Education Study Program, Faculty of Art and Design, Makassar State University in creating graphic arts using woodcut techniques as the most basic and simple technique compared to other printing techniques. In addition, it is also to find out the factors that influence the ability to work in woodcut graphic art techniques in students. Data were collected through field studies, namely through questionnaires, observations, practical tests, and documentation/photos. The results showed that the ability of students of class 2011 in creating woodcut technique printmaking as a whole was said to be very good. Students who get error scores are caused by incomplete work assignments, not because their work is not good, and lazy to take printmaking classes. Factors supporting the work process, namely the right method, allocation of work time, and the high interest and motivation of students in creating graphic arts. The inhibiting factors, namely the frequency of work experience is very minimal, namely as the first experience so that it is quite difficult both in the use of tools and in the practice of work.